Payment methods and their effect on durable goods replacement. Issue 4 (2nd April 2019) - Tatavarthy, Aruna Divya; Mukherjee, Kanchan
Abstract : Purpose: Unlike point of purchase behavior, not much is known about how payment method impacts post-purchase behavior, especially for durable goods where user experience can last over long periods. The purpose of this paper is to link two strands of literature for the first time by uncovering systematic linkages between the payment method (upfront cash vs loan) used for purchase of durable goods and the replacement timings for the same. Design/methodology/approach: The authors predict that cash purchases are more likely to have shorter replacement horizons compared to loan purchases and propose a psychological mechanism that accounts for the same. Their arguments are based on how the strength of coupling, which is the degree of psychological association between payment and consumption, depends on the payment method and differentially influences the consumption experience and consequently leads to different replacement horizons. They conduct a field study to test their predictions and find support for their model. Findings: The authors find that individuals who financed their durable goods purchases using loan, expressed their intentions to replace the goods after longer period than those who financed their durable goods with cash down payment. As loan installments remind people of painful thoughts of payment, they tend to reduce the dissonance by positively evaluating both retrospective and anticipated usage experiences. This dissonance reduction mechanism eventually leads to reduced willingness to let go of the durable. Practical implications: Marketers are faced with a tradeoff between increasing purchase likelihood versus ensuring long-term post-purchase satisfaction. In this paper, the authors uncover the psychological mechanisms that can explain how payment method chosen to pay for a durable can have direct effect on post-purchase consumption experiences and subsequently in the replacement intentions. This finding is crucial for marketers who are interested in planning the product line launches and other post-purchase engagement strategies such as buy-back scheme and upgrades. Social implications: Understanding the psychological mechanisms that explain individual's likelihood to replace their durable goods allows policymakers to design appropriate interventions to induce more sustainable and efficient use of durable goods in the market. While on one hand, marketers might be interested in increasing sales of their product line by inducing faster replacement of older product versions, environmentalists nudge towards the opposite. This paper provides a possible way to achieve the dual objectives. Originality/value: While past research on downstream effects of payment methods on behavioral outcomes focused only on consumables, the authors focus on durable goods. Further, they identify the effect of payment method on both psychological and behavioral outcomes.